The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/pr11020445
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Bonding Strength of Finger Joints Using a New Test Specimen Geometry

Abstract: In this study, a specimen geometry for testing finger joints was developed using finite element simulation and proofed by experimental testing. Six different wood species and three adhesives were used for finger-jointing specimens. With the test specimen geometry, the bonding strength of the finger joints was determined without the usual self-locking of the joint. Under load, the test specimen geometry introduces maximum stress at the beginning of the bond line (adhesive zone). However, the test specimen geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In recent years, many scholars have updated the joint structure to further improve the adhesive performance of joints and expand the scope of application of colloidal connections. Stolze et al 78 used a new type of finger joint, as shown in Figure 5(a) , to investigate the adhesion properties of six different substrates to three different adhesives. However, this joint also does not avoid stress concentration, and the angle and length of the finger joint affect the stress distribution.…”
Section: Joint Design Strategy and Failurementioning
confidence: 99%
“…In recent years, many scholars have updated the joint structure to further improve the adhesive performance of joints and expand the scope of application of colloidal connections. Stolze et al 78 used a new type of finger joint, as shown in Figure 5(a) , to investigate the adhesion properties of six different substrates to three different adhesives. However, this joint also does not avoid stress concentration, and the angle and length of the finger joint affect the stress distribution.…”
Section: Joint Design Strategy and Failurementioning
confidence: 99%